Isolated skill test battery for actual aquatic skillacquisition in children (6-12y) within the european alfac("aquatic literacy for all children") project - Martelaer, D. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The Aquatic Literacy for All Children (ALFAC) research project investigates aquatic skills, knowledge and psychosocial domains to improve drowning prevention, motor development and a long live involvement in children (6-12y). As a part of the evaluation of aquatic skills acquisition a large-scale test battery was developed. Stallman et al.'s (2017) model describes the fundamental aquatic skills (FAS) to be mastered. Inspired by the work of Stallman et al. (2017), the Pictorial Scale of Perceived Water Competence (Morgado et al., 2020) and the Assessment of Basic Aquatic Skills (Vogt & Staub, 2020), the ALFAC team selected 10 isolated skills: (1) entry in the water, (2) exiting the water, (3) breathing, (4) treading water, (5) floating on the back, (6) propulsion on the back, (7) propulsion on the belly, (8) submersion, (9) rotation in horizontal body position, (10) rotation in vertical body position. Researchers also intended to facilitate a competent and confident movement experience in the exciting and diverse water environment. Therefore, the face and content validity and the feasibility in the selection and development of isolated tests was crucial. Tests not adapted to real life situations might lead to frustration and/or a false feeling of security. Therefore, stimulating pleasure and confidence to children discovering the aquatic environment in a safe and fun manner is the path to follow. Special attention was also given to the reality of different technical conditions in swimming pools by choosing the same material to create equal environments in all test sites in different EU partner countries. For example, to tackle the variability in the height of the edge, a standardized floating platform is used. The test battery of the isolated skills has also to be integrated into the complete holistic tool of ALFAC. E.g., the same test items were used for children`s self-perception about the aquatic skills, which is part of the questionnaire. The third and final part will be a `parcours` where the same skills are tested in a playful combination, where children must make individual decisions to stop or continue the challenge while swimming. Development of the test battery and some first data of the pilot study on the 10 isolated skills in this EU project will be presented at the conference.